2017
DOI: 10.1016/j.jnucmat.2017.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of Ar ions irradiated nanocrystalline ZrC and ZrN thin films

Abstract: Thin nanocrystalline ZrC and ZrN films (<400 nm), grown on (100) Si substrates at a substrate temperature of 500 °C by the pulsed laser deposition (PLD) technique, were irradiated by 800 keV Ar ion irradiation with fluences from 1 × 10 14 at/cm 2 up to 2 × 10 15 at/cm 2 . Optical reflectance data, acquired from as-deposited and irradiated films, in the range of 500 -50000 cm −1 (0.06 -6 eV), was used to assess the effect of irradiation on the optical and electronic properties. Both in ZrC and ZrN films we obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Optical reflectance measurements and high energy X-ray photoemission spectroscopy (HE-XPS) were used to study the effect of 800 keV Ar ion irradiation on the optical and electronic properties of nanocrystalline ZrC and ZrN thin films obtained using the pulsed laser deposition technique. 65 It was observed that irradiation affects the optical properties of the films primarily at low frequencies, which is dominated by the response of free carriers. A significant reduction in the free carrier scattering rate and an increase in zero frequency conductivity, i.e.…”
Section: Refractive Index and Aestheticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical reflectance measurements and high energy X-ray photoemission spectroscopy (HE-XPS) were used to study the effect of 800 keV Ar ion irradiation on the optical and electronic properties of nanocrystalline ZrC and ZrN thin films obtained using the pulsed laser deposition technique. 65 It was observed that irradiation affects the optical properties of the films primarily at low frequencies, which is dominated by the response of free carriers. A significant reduction in the free carrier scattering rate and an increase in zero frequency conductivity, i.e.…”
Section: Refractive Index and Aestheticsmentioning
confidence: 99%
“…24,25,26,27,28 Erosion behavior of ZrN coatings was studied in 1988 29 and 1990. 30 Various studies were conducted on ZrN coatings in the following decades to evaluate their various properties such as tribology, 31,32,33,34,35,36,37,38 erosion, 39,40,41 adhesion, 31 structure, composition, corrosion and oxidation, 42,43,44,45 nuclear fuel element compatibility, 46,47,48 color of coatings, 49 influence of synthesis parameters, 50,51,52,53 bio-and cyto-compatibility of human body implants, 54,55,56,57,58,59,60 optical, electrical and electronic properties, 61,62,63,64,65 and modeling and computational analysis. 66,67,68 Various investigations on Zr-carbonitride coatings have been undertaken to study synthesis parameters, 69<...>…”
Section: Introductionmentioning
confidence: 99%
“…For nuclear applications, it is necessary to investigate the effect of radiation on the ZrN films composition, structure and properties. The effect of neutrons, ions and protons irradiation on ZrN has been recently investigated [8,[16][17][18][19][20][21][22][23][24]. New results indicated that nanocrystalline materials could be more tolerant to radiation damage than large grain or single crystal materials.…”
Section: Introductionmentioning
confidence: 99%
“…New results indicated that nanocrystalline materials could be more tolerant to radiation damage than large grain or single crystal materials. Since ZrN films could be grown as a nanocrystalline film with grain sizes around 10 nm, there has been renewed interest to study the effect of radiation on such materials [8,17,18,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation